Identification of Novel Genes and New Breeding Techniques for Crop Improvement - Roja, V.; Rani, Ch.; Suresh, M.; Satyanarayana, N. Hari; Babu, J. Sateesh; Pranaya, J.; Sudhamani, K.; Tushara, M.; Bindiya, Y. (Chronicle of Bioresource Management, 2024)
The global population is expanding rapidly, projected to reach 10 billion by 2050. This necessitates an increased focus on producing sufficient grains to address global food and nutritional security. To effectively tackle future food security challenges, it is crucial to explore new genetic resources to identify potential novel genes for enhancing the yields. The exploration of crop wild relatives serves as a solution for discovering novel genes, with next-generation sequencing technologies facilitating efficient gene identification in major crop and wild species to enhance crop improvement. The CRISPR/Cas9 system has emerged as the predominant tool for crop breeding, while speed breeding methods offer additional avenues for the rapid development of new crop varieties. These techniques have become powerful resources, poised to advance plant breeding and contribute to a second green revolution. Their application is vital in meeting the food demands of a rapidly growing global population, especially in the face of ever-changing climate conditions.